Vitamin D and gut microbiome in preterm infants - Putri Maharani Tristanita Marsubrin; Agus Firmansyah; Rinawati Rohsiswatmo; Yuditiya Purwosunu; Saptawati Bardosono; Safarina G. Malik; Zakiudin Munasir; Ina S. Timan; Tetty Yuniati; Maya Yulindhini (BMC, 2024)
Abstract Background The incidence of vitamin D deficiency among pregnant women remains high and is associated with vitamin D deficiency in infants. In normally breastfed infants, Bifidobacteriaceae and Lactobacillaceae are known to help in maintaining immunotolerance and prevent infection. Vitamin D in the gastrointestinal tract plays a role in determining the composition and function of intestinal bacteria. Preterm infants are vulnerable to intestinal dysbiosis and sepsis due to bacterial translocation. This study aimed to determine the association between vitamin D levels and intestinal dysbiosis. Methods It was a cohort study conducted in the Neonatal Unit, Cipto Mangunkusumo Hospital, Tertiary hospital in Indonesia, from November 2019 to January 2021. The inclusion criteria in this study were preterm infants with a gestational age of less than 32 weeks or a birth weight of less than 1500 g. Total 25-hydroxyvitamin D (25(OH)D) levels were collected from the umbilical cords of very preterm or very low birth weight infants. A fecal examination was performed on the seventh day of life to assess intestinal bacteria using real-time PCR for four bacterial genera: Bifidobacteriaceae, Lactobacillaceae, Enterobacteriaceae, and Clostridiaceae. Results A total of 43 infants were included in this study. Among the subjects, 53.4% had vitamin D deficiency. There was no association identified between vitamin D deficiency and intestinal dysbiosis (RR 0.67; 95% CI (0.15-2.82), p-value = 0.531). However, the ratio of Lactobacillacecae to Enterobacteriaceae was lower in those with vitamin D deficiency. Conclusion Vitamin D deficiency was not associated with dysbiosis in preterm infants. However, this study found that the ratio of Lactobacillaceae to Enterobacteriaceae in those with vitamin D deficiency was lower than in those without vitamin D deficiency. Further research is warranted to confirm this finding.